Description of a new species of Hisonotus (Loricariidae: Siluriformes) from rio Araguaia basin - Ribeiro-Silva, Luis R. [UNESP] (2020)
A new species of Hisonotus is described from headwaters of rio Araguaia basin, municipality of Barra do Garcas, Mato Grosso state, Brazil. The new species is distinguished from its congeners by a V-shaped spinelet, yellowish teeth, absence of unpaired platelets at typical adipose fin position, the caudal-fin color hyaline with three transverse dark bars, one abdominal median plate series, and by morphometric and meristic characters.